Case Report: “Aggressive” perioperative antiseizure medication prophylaxis in patients with glioma-related epilepsy at high risk of early postoperative seizures following awake craniotomy - Freund, Brin E.; Jaeckle, Kurt; Quinones-Hinojosa, Alfredo; Feyissa, Anteneh M. (Frontiers in Surgery, 2024)
Early postoperative seizures (EPS) are a common complication of brain tumor surgery. EPS can lead to hemorrhage, cerebral hypoxia, increased intracranial pressure, longer hospitalization, reduced quality of life, decreased overall survival, and increased morbidity. However, there is little guidanceno formal guideline on perioperative antiseizure medication (ASM) management in patients with tumor-related epilepsy deemed high risk for EPS. We describe a 38-year-old man with IDH-mutant mixed glioma and two episodes of EPS manifesting with status epilepticus (pSE) during prior tumor surgeries presented with tumor progression. The Tumor Board recommended awake craniotomy with direct electrical stimulation (DES). He received aggressive preoperative "prophylactic" ASMs by increasing maintenance doses of lacosamide and levetiracetam by 25% 48 hours before surgery. An intravenous load of fosphenytoin (20 mg/kg) was given in the operating room before DES, followed by a maintenance dosing of 300mg/day for 14 days. EPS did not occur, and he was discharged home on postoperative day 4. Our case illustrates that aggressive perioperative prophylactic ASM therapy beyond maintenance ASM regimen can be considered could potentially prevent EPS in patients with tumor-related epilepsy at risk for EPS.